Morphological evidence supports splitting of species in the North Atlantic Sebastes spp. complex - Ingrid Marie Bruvold; Agneta Hansen; Arve Lynghammar; Hannes Höffle; Tanja Hanebrekke; Caroline Aas Tranang; Kjell Nedreaas; Einar Nilssen; Atal Saha; Torild Johansen (PLoS ONE, 2025)
The redfishes (genus Sebastes) are long-lived, commercial species in the North Atlantic. Excessive harvest through decades has led to a decline in the mature population of golden redfish (Sebastes norvegicus) in Norwegian waters, which is currently considered severely depleted. Accumulating genetic evidence suggests a more complex structure within this genus in the North Atlantic, which has recently inspired the hypotheses of cryptic species within S. norvegicus. Despite apparent genetic divergence between two types, they have yet to be verified morphologically. The morphology of genetically assigned fishes from Norwegian and Greenland waters was investigated using traditional morphometric methods, applying Linear Discriminant Analysis and Random Forest classification procedures to identify and evaluate the performance of descriptive characters. Combined with non-parametric meristic analysis, the results show that features such as beak length and eye diameter provide sufficient discrimination between the proposed cryptic species as well as separating them from the sympatric species S. mentella and S. viviparus. These findings support the presence of an additional redfish species in the North Atlantic, distinguishable both by morphological and genetic characters. This needs to be taken into consideration in future monitoring and management strategies for North Atlantic redfish.